Effect Of Promotion Strategy, Price, Advertising, Quality Service, Customer Trust On Seafood Purchase Decision In Batam Mediation By Product Quality - Hasan, Golan; Leon, Winson (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Batam City is a zone of territory that is surrounded by the ocean so it is called an archipelago. And also surrounded by Singapore and Malaysia. Making the city of Batam a strategic position. And because Batam city is an archipelago, Making Batam City rich in culinary tourism especially on seafood. Batam City is also known as paradise for seafood lovers because Batam City has a very large and rich supply of seafood. Seafood is a food that produces a source of animal protein and omega 3 which is beneficial for our health. Therefore, culinary tourism especially seafood restaurants is a promising business in Batam City. Seeing the prospect and high demand for seafood, The seafood restaurant business is also growing and increase in Batam City. This research aims to analyze the effect of Promotion Strategy, Price, Advertising, Quality Service, Customer Trust, on Purchase Decision with mediation of Product Quality in Batam City. This research was conducted by distributing questionnaires by google form and the total of the samples used in this study were 400 respondents. This study was analyzed using smart PLS version 3.